A constituição do ethos feminino em A Bolsa Amarela, de Lygia Bojunga - Estracieri, Elaine Aparecida dos Santos (2015)
This work is part of the research line Text and Discourse on Oral and Written Procedures , the Postgraduate Program in Portuguese at the Pontifical Catholic University of São Paulo. The Theme of this research is The constitution of the feminine ethos in The Yellow Bag , Lygia Bojunga and born of the initial belief linked to the construction of social discourses. In this paper we analyse a literary work here considered as a representation of the world through words. In the discursive level, it is the female speech introjection that rhetorical tricks, as they reflect the being in existence, leverage the instituting discourse and sediment, by moving the passions, new ways of saying and understand the world. The Yellow Bag, published in 1976, still reverberates powerfully valid one speech to think the status of women today in presenting indisputable rhetorical force in the development of the main character s arguments, Rachel girl. Thus, the analysis undertaken in this study adopts a perspective centered in the speech of female character-child, by checking a rhetorical process of constituting an ethos created fictitiously by an adult, the writer Lygia Bojunga. As we observed, handling the language the author demonstrates enough discursive ability to move within the limits of a literary text, the dominant discourse and create instituting apeeches that highlight the condition of being a woman in today s world. Raquel, through the rant, makes its effective argument, causes the pathos (passion) and the auditorium, by setting out a line originated from the interior of a child, it becomes benevolent with the narrated facts. For present itself in the robes of a literary text, passion compels the audience to accept one or more conclusions about a woman nowadays. This attitude of acceptance presupposes driving through reasoning, albeit sharp appeal to the listener s emotions. The analysis addresses, then two facets: the recreation of speech in child communicative interaction situation and fictional view of how a child is imposed discursively to constitute its ethos in the narrative. Constituted as an analytical base studies of Aristotles (2000), Perelman and Olbrechts-Tyteca (2005), that guide research Reboul (2004), Meyer (2007) and Ferreira (2010). To create the historical context, draws up an overview of women, children and the family, through Bassanezi studies (1986), Aries (2012) and Santarcangelo (1980). For proof of persuasive means, analyses through features allowed by the rhetoric analisys, the efficacy of the speech by the girl-woman speaker called Raquel. At the end of the investigation it was concluded that, in the Yellow Bag, as imagined in the case of this study, the condition of women, historically marked by devaluation, submission and subservience, is partially abandoned to make way for discursive construction of a scenario that portends changes social and significant contemporany female professionals in the act. It appears, too, that the character Rachel is constructed rhetorically to highlight an ethos that seduces (movere) the auditorium to present as girl-child (delectare) and proposes questions that culminate in reflections (docere) to the auditorium